Indicadores de qualidade do solo e sua relação com a produtividade em sistemas integrados de produção agropecuária em plantio direto - Laroca, Jackeline Vieira dos Santos (2018)
The objective of the work was to evaluate the influence of the consortia with leguminosas in the phase pasture of SIPA-PD in the increment of organic matter, in the activity microbiológica of the soil and productivity of grains and production and quality of the pasture. And to identify the indicators of quality of the soil with influences in the changes of the productivity of the system. The experiment was driven in Itiquira (MT) in a Latossolo Red distrófico, where they were implanted, after crop of the soy, the treatments with grassy Urochloa ruziziensis, U. brizantha to cultivate BRS Paiaguás, Panicum maximum to cultivate BRS Tamani and U. brizantha to cultivate BRS Piatã cultivated unmarried and associated with bean caupi (Vigna unguiculata) to cultivate BRS Tumucumaque and bean guandu (Cajanus cajan) to cultivate BRS Mandarim. The experimental delineamento was of blocks casualizados with three repetitions in outline of subdivided portions where the grassy ones were considered as portions and the subparcelas were represented by the leguminosas. It was verified that the consortia provided increments in the tenors of C and N as well as in their fractions particulate and in the index of handling of carbon. C and N of the microbial biomass were also increased by the adoption of the consortia with leguminosas, and the single cultivations presented high values of basal breathing and metabolic quotient, evidencing stress in the microbiota of the soil. Plant productivity was positively influenced by consortiums with cowpea. Dry matter and crude protein have a positive and significant influence on animal production. And the C of the microbial biomass followed by the N in the organic matter was used in the tests that improved explicitly as the changes in productivity. The Paiaguás and Piatã grasses intercropped with leguminous cowpea beans provide greater increases in attributes related to soil quality, also reflecting the higher yields of the system.